2016
DOI: 10.1111/cen.12993
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term treatment with pegvisomant for acromegaly: a 10‐year experience

Abstract: We reassure the efficacy and safety of long-term PEG. An escape phenomenon may occur, but it can be overcome by adjusting therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
1
9
1
1
Order By: Relevance
“…7 Another study reviewed the efficacy of pegvisomant as a monotherapy for acromegaly over a 10-year period, and showed 6 of 64 (9.4%) cases with tumor growth. 123 Pegvisomant has also been evaluated in a combination therapy with SRL, particularly with respect to normalizing the IGF1 concentration in acromegalic patients who have failed SRL monotherapy. The outcome of a 42-week study of active acromegalic patients demonstrated that the combined therapy was effective in normalizing the levels of IGF1 and that there was no indication of tumor growth.…”
Section: Strategies That Target Ghr Signalingmentioning
confidence: 99%
“…7 Another study reviewed the efficacy of pegvisomant as a monotherapy for acromegaly over a 10-year period, and showed 6 of 64 (9.4%) cases with tumor growth. 123 Pegvisomant has also been evaluated in a combination therapy with SRL, particularly with respect to normalizing the IGF1 concentration in acromegalic patients who have failed SRL monotherapy. The outcome of a 42-week study of active acromegalic patients demonstrated that the combined therapy was effective in normalizing the levels of IGF1 and that there was no indication of tumor growth.…”
Section: Strategies That Target Ghr Signalingmentioning
confidence: 99%
“…In fact, two large comprehensive reviews exploring this issue concluded that control of GH and IGF-I excess could halt the progression of cardiovascular abnormalities, as well as the observed morphological and functional cardiac alterations (58, 89). Additionally, concomitant cardiovascular risk factors, such as hypertension, dyslipidemia, diabetes mellitus, and sleep apnea syndrome, could also improve (28, 9294). Epidemiological data have confirmed these findings, and disease control in acromegalic patients has been found to be one of the most important determinants of patients' outcome (5), and consistently associated to a reduction in cardiovascular mortality (1, 2, 55).…”
Section: How Does Disease Control Affect Cardiovascular Comorbiditiesmentioning
confidence: 99%
“…In fact, treatment of acromegalic patients with pegvisomant improved left ventricular mass, systolic and diastolic function and blood pressure, reduced the prevalence of conduction disturbances, and even decreased the Framingham risk score after 12 months of treatment in the German Pegvisomant Observational Study (121, 123125). Furthermore, the reduction in levels of glucose, insulin, and HOMA index may be relevant for its overall beneficial role (94, 119, 120), because of the collateral effect on glucose homeostasis.…”
Section: How Does Disease Control Affect Cardiovascular Comorbiditiesmentioning
confidence: 99%
“…If the adenoma grows, a somatostatin analogue can be used [34]. Pegvisomant is administered subcutaneously on a daily basis at 10-30 mg as monotherapy or in combination with a somatostatin analogue [32,34,35].…”
Section: Continue Therapy Control Development Of Disease Complicationsmentioning
confidence: 99%
“…Pegwisomant nie wpływa korzystnie na wielkość guza przysadki i z uwagi na ryzyko powiększania się gruczolaka w czasie leczenia konieczna jest kontrola jego objętości za pomocą MR. W przypadku powiększenia się gruczolaka można dodatkowo zastosować analog somatostatyny [34]. Pegwisomant podaje się codzienne, w dawkach 10-30 mg podskórnie w monoterapii lub łącznie z analogiem somatostatyny [32,34,35].…”
Section: Wytyczneunclassified